2021
DOI: 10.1016/j.ygyno.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of marital status on stage at diagnosis and survival of female patients with breast and gynecologic cancers: A meta-analysis

Abstract: Marital status of female cancer patients has an impact on diagnostic timeliness and prognosis • The unmarried female cancer patients are associated with late stage at diagnosis and worse prognosis • Among female cancer patients with high level of social support, the unmarried had worse survival outcomes than the married • From the perspective of public health, more health attention should be paid to unmarried women with cancer

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
4
15
0
Order By: Relevance
“…Univariate and multivariate analysis showed that marital status significantly impacted survival in UTUC with bone metastasis. Many studies have shown that marital status is an important factor affecting the prognosis of cancer patients, and married patients generally have a better prognosis due to the economic and emotional support ( 25 27 ). Married patients were more likely to gain curative treatment, high-quality care, and support of their spouse ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Univariate and multivariate analysis showed that marital status significantly impacted survival in UTUC with bone metastasis. Many studies have shown that marital status is an important factor affecting the prognosis of cancer patients, and married patients generally have a better prognosis due to the economic and emotional support ( 25 27 ). Married patients were more likely to gain curative treatment, high-quality care, and support of their spouse ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results highlight the importance of reducing health disparities in the unmarried population. A meta-analysis assessing the impact of socio-economic factors on stage at diagnosis and survival of female patients with gynecological cancers found a 28% increased risk of late-stage diagnosis and a 20% higher risk of death among unmarried female cancer patients, confirming the significant protective effect of marriage against mortality associated with gynecological cancers [Yuan et al, 2021]. The protective effect of marriage may be explained by lifestyle and health-related behaviors, as close partners may recognize cancer-related symptoms in time and encourage their spouse to participate in screening or seek medical advice [Osazuwa-Peters et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were never married or in other marital statuses had a higher risk of all-cause death, kidney cancer-specific death, and other noncancer deaths than married patients. The fact that marriage provides social support may partly explain this finding ( 14 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with stage IV disease had a higher SMR in heart disease than those with stage I/II and III (SMR, 1.92; 95% CI, 1.72–2.14 for stage IV; SMR, 1.23; 95% CI, 1.14–1.32 for stage III; SMR, 1.23; 95% CI, 1.19–1.27 for stage I/II). In the past decade, several tyrosine kinases and vascular endothelial growth factor inhibitors have been used for first-line therapies in patients with metastatic RCC ( 13 , 14 ). These drugs greatly improved the survival rate of patients with metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%